The administration of supplements milk with high protein of whey increased estrogen level but did not affect testosterone level in male wistar rat (Rattus norvegicus) - Dian Andriani; Wimpie Pangkahila; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2019)
Introduction: Supplements milk is a high protein of whey that consumed by many teenagers to maintain the fitness in accordance with the advertisements in the society, the presence of hormones in milk that are not listed in its composition causes a hormonal balance disorder. The aim of this research was to prove that giving supplements milk with a high protein of whey in increasing estrogen levels and lowers testosterone counts in male Wistar rats (Rattus norvegicus). Methods: This research employed experimental research using a pretest-posttest control group design that used 22 white male Wistar rats (Rattus norvegicus), the samples were divided into 2 groups, namely the control group (P0) and the treatment group (P1) that treated by supplements milk with a high-protein of whey once a day for three weeks. The blood was taken before and after treatment for estrogen levels and testosterone counts. Result: The finding indicated that a significant increase in estrogen levels before and after the administration of milk supplement with high whey protein 11.603 ± 0.502 ng/ ml to 16.141 ± 0.347 ng/ ml (p<0.001). There was no decrease in testosterone counts before and after subjects were administered by milk supplement with high whey protein 1.86 ± 0.325 ng/ ml to 1.69 ± 0.260ng/ ml p = 0.220 (p> 0.05). Conclusion: Based on the results of the analysis it could be concluded that the administration of milk supplement with high whey protein could increase estrogen levels while decreasing testosterone in male Wistar rats (Rattus norvegicus).